About Indispensable or Irreplaceable People in School Management: Perspectives and Possible Addresses in Current Institutional Contexts. Rosario, Argentina, 2004-2014 - Tranier, José A. (2014)
In this paper, we will try to ask about the relationship between the new social and political logics that took place in the early twenty first century in Argentina and its ways of re translation into concrete educational practices performed by teachers at school. In order to reach this, we proposed a critical hermeneutic approach based on the telling of some experiences and participant observations of many different actors and, also, from the universe of the practices that, throughout the contributions of critical authors, let us identify some underlying meanings regarding particular ways of management at school. In few words, we were interested in try to link the educational processes that took place throughout the recent history at schools and its changes deployed in that specific, complex, social and political context.